Comparative Analysis of the Costs (RAB) Budget Development Project in Surabaya - Arik Krismawanto; Fredy Kurniawan (LPPM NAROTAMA UNIVERSITY, Indonesia, 2019)
In the construction of a building, one of which is a mosque, it does require efficiency on the budget plan, so that development can be completed to the maximum with optimal time and little cost. The purpose of this study is to find out the ratio of labor wage coefficients between the Budget Plan (RAB), BOW and Implementation; Knowing the comparison and the difference in the number of unit prices of labor wages; Find out the cause of the difference in price. Data processing is done by literature method, documentation, conducting field observations and conducting interviews. The results of the work include formwork column K1 (thread D19) foreman coefficient ratio in RAB Offer with Implementation that is equal to 1.21, while BOW with Implementation is 0.37. Then for the wages of reinforced concrete deck work Lt. 2 12cm thick K-250 with an area of ??41.05 m3 the difference between the RAB of the Offer and the Implementation of Rp. 36,263,855.91 (64.4%), while the difference between BOW and Implementation is Rp. 138,619,043.82 (87.4%). The magnitude of the ratio of ratios and differences in the budget for wage costs is influenced by many factors: labor wage prices, quantity or amount of labor used in the project, skill level and age of the workforce, and high interest in workforce employment.